The effect of oral administration of choline on some liver function characterized blood plasma enzymes of early lactating dairy cows - M. G. Rahmani; R. G. Kamalyan; M. J. Dehghan-Banadaky; G. Yu. Marmaryan (ՀՀ ԳԱԱ հրատ.)
Sixteen early lactating primiparous and multiparous Holstein cows were used for four weeks to investigate the effects of feeding choline on the activity of aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP) and γ-glutamyltransferase (GGT) in the plasma of the cows during early lactation period. Cows were randomly assigned to one of the following treatments: no supplement (control) and 90 g/d of rumen-protected choline (RPC) product. Treatments did not affect significantly ALT, AST and GGT during early lactation period, but for ALP there was a significant difference between the groups. The research results showed significant influence of feeding protected choline on ALP. Առաջնածին և բազմածին Հոլշտեյն ցեղի 16 կովերի վրա ուսումնասիրվել է կտրիչի ազդեցությունից պաշտպանված խոլինի ազդեցությունը լյարդի ֆունկցիան արտահայտող արյան պլազմայի ասպարտատ- և ալանինտրանսամինազ (ԱՍՏ, ԱԼՏ), հիմնային ֆոսֆատազ (ՀՖ) և γ-գլյուտամիլտրանսֆերազ (ԳԳՏ) ֆերմենտների ակտիվության վրա: Կովերը բաժանվել են 2 խմբերի` I — ստուգիչ (առանց հավելումի), II — փորձնական (օրական ստացել են 90գ խոլին) վաղ լակտացիայի շրջանի 4 շաբաթվա ընթացքում: Խոլինի կերակրումը վաղ լակտացիայի շրջանում չի ազդում արյան պլազմայի նշված ֆերմենտների ակտիվության վրա, բացի ՀՖ-ից, որի ակտիվությունը հավաստիորեն նվազում է: В опытах были использованы 16 первотелoк и многократно рожавших коров породы Голштейн, которым в ранний период лактации вскармливали холин в течение 4-х недель. Коровы были разбиты на 2 группы: I-контрольная (без добавок), II-получавшая 90 г холина в день. В плазме крови определяли активность аспартат- и аланинтрансаминаз (АСТ и АЛТ), щелочной фосфатазы (ЩФ) и γ-глутамилтрансферазы (ГГТ) в ранний период лактации. Добавка холина не отражалась на активности трансаминаз и ГГТ, однако вызывала статистически достоверное уменьшение активности ЩФ в ранний период лактации.
Keywords: Biology; Zoology